Analisis Implementasi Total Quality Mangement dalam Pelayanan IGD RSUD Kota Dumai - Indra Kurniawan; Budi Hartono; Lita Lita; arnawilis arnawilis; Jasrida Yunita (Jurnal Kesehatan Komunitas, 2022)
Total Quality Management is one approach that helps hospitals to improve service quality. There are many factors that influence TQM, namely customer focus, teamwork, continuous improvement, education and training, employee involvement and empowerment. This study aims to determine the implementation of TQM in the emergency department of the Dumai City Hospital as well as the factors influencing it. This type of quantitative analytic research uses a Cross Sectional design. The research population is doctors and paramedics who work in the ER at the Dumai City Hospital using purposive sampling with a sample of 57 respondents. Data was obtained by filling out questionnaires. Data analysis using univariate, bivariate, and multivariate presented in the form of frequency distribution. The results of the analysis show that there is a relationship between focus on customers, continuous improvement, involvement and empowerment of employees with the implementation of TQM in Dumai City Hospital. While the other two factors, namely teamwork and aspects of education and training there is no relationship. To realize a better TQM implementation, three related variables need to be improved.